Tourist Satisfaction with Service Quality at the Agung Besakih Temple Tourist Attraction-Karangasem - Suandari, Gusti Ayu Intan Sri; Agustini, Ni Putu Oka; Wiarti, Luh Yusni (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
Tourist satisfaction with service quality is measured through 5 dimensions, namely: Tangible, Reliability, Responsiveness, Assurance, and Empathy consisting of 20 indicators. The purpose of this study was to determine tourist satisfaction with service quality at Pura Agung Besakih. This study uses quantitative descriptive analysis using a questionnaire and a Likert scale with a purposive sampling technique with a total of 100 respondents. The average value of X (service performance) is 3.52 and Y (expectation) is 3.62. Each dimension is in the appropriate category but Y> X which causes tourist dissatisfaction. The research results can be interpreted by the Importance Performance Analysis (IPA) analysis using 4 quadrants where in quadrant I there are indicators: 5, 13, 14, 16, quadrant II: 1,3,4,8,10,15,17, 19, quadrant III: 6,7,9,11,20, Quadrant IV: 2, 12, 18.